Os fundos do Public Record Office e da British Lybrary enquanto complemento dos arquivos nacionais para a história do vinho do Porto - Cardoso, António Barros (2003)
The strong connection between Portugal and England that, in the eighteenth century was deeply developed due to the business of the Port Wine implies an attentive study of the portuguese history for the British Archives. In this study, besides the brief references to the history of the political-diplomatic connections between the two countries, we tried to shed light on the main documents kept in the British Library and in the Public Record Office. These help in the history of the Port wines that were sent to the British ports under the designation of "Porto".